Forgotten Conflicts: Producing Knowledge and Ignorance in Security Studies. Issue 1 (15th September 2021) - Brenner, David; Han, Enze
Abstract: Security studies privileges the study of civil wars in some contexts over others. The field's leading journals mostly publish studies of armed conflicts in Africa, Eastern Europe, and the Middle East. Armed conflicts in Asia receive comparatively little attention, despite their prevalence and protracted nature. Against the background of our own empirical archive—the decades-old but largely ignored civil war in Myanmar—we ask why some conflicts draw more scholarly interest than others and why this uneven attention matters. In doing so, we argue that the empirical selectivity bias in the study of civil war and armed conflict reflects (1) institutional entanglements between the field of security studies and Western foreign policy; and (2) sociological factors that shape the formation of scholarly subjectivities and pertain to methodological challenges. This uneven empirical landscape shapes our conceptual understanding of civil wars. In fact, prominent debates within leading security studies journals surrounding the nature of civil war and armed conflict are inseparable from the empirical contexts in which they emerged. Leveling such an uneven empirical landscape thus generates opportunities for discussing conflict, insecurity, and violence in a different light. In shedding light on this issue, we urge closer attention to questions of place, time, and power in the scholarly production of knowledge and ignorance.